Plantation memories : episodes of everyday racism - Kilomba, Grada (Münster : UNRAST-Verlag, 2020)
"Plantation Memories is a compilation of episodes of everyday racism written in the form of short psychoanalytical stories. From the question "Where do you come from?" to Hair Politics to the N-Word, the book is a strong, eloquent, and elaborate piece, which deconstruct the normality of everyday racism and exposes the violence of being placed as the Other. Released at the Berlin International Literature Festival (2008), soon the book became internationally acclaimed and part of numerous academic curricula. Known for her subversive practice of giving body, voice and image to her own texts, Kilomba adopted her book into a staged reading (2012) and video installation (2018). This fifth edition coincides with the 10th anniversary of the book release, celebrating Plantation Memories as an important contribution to the global cultural discourse." --taken from back cover.
Chapter 1. The Mask -- Chapter 2. Who can speak? -- Chapter 3. Speaking the unspeakable -- Chapter 4. Gendered racism -- Chapter 5. Space politics-- Chapter 6. Hair politics -- Chapter 7. Sexual politics -- . Chapter 8. Skin politics -- Chapter 9. The N-word and trauma -- Chapter 10. Segregation and racial contagion -- Chapter 11. Performing blackness -- Chapter 12. Suicide -- Chapter 13. Healing and transformation -- Chapter 14. Decolonizing the self -- Literature.
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
boek